Increasing Diagnosis Rates and the Changing Etiology in Childhood Pancreatitis; Ten Years of a Single-Center Experience in Turkey - Sevim Çakar; Gülin Eren; Neslihan Pirinç; Cahit Barış Erdur; Çiğdem Ömür Ecevit; Özlem Bekem (Galenos Yayinevi, 2023)
Aim:In this study, we aimed to evaluate the etiological, clinical, and laboratory characteristics of children with pancreatitis and the changes in these data over the years.Materials and Methods:Children hospitalized with a diagnosis of pancreatitis between January, 2011 and January, 2021 were evaluated retrospectively. The etiology, demographic characteristics, laboratory findings, and changes over the years were analyzed.Results:A total of 111 cases were enrolled, 72 (64.9%) in the acute pancreatitis (AP) group and 39 (35.1%) in the acute recurrent pancreatitis and chronic pancreatitis (ARP/CP) group. The most common causes of AP were idiopathic (27.8%), cholelithiasis (26.4%), and infections (8.4%). In ARP/CP assessments, idiopathic (35.9%), trauma (15.4%), and drugs (10.3%) were the most frequent etiologies. During the first five-year period, only 14 patients were diagnosed with pancreatitis, but in the second five years, 97 patients were diagnosed with pancreatitis. In both periods, the most frequent diagnosis was idiopathic pancreatitis (42.9% and 28.9%, respectively). While trauma (14.3%) and infections (14.3%) were the most common etiologies in the first five years, cholelithiasis (20.6%) and drugs (9.3%) were the most common in the second five years.Conclusion:There was a significant increase between the first and the second five-year periods in pancreatitis-related hospitalizations. The most common cause of pancreatitis in all groups was still unknown. The cholelithiasis ratio increased from 7.1% to 20.6% in the second five-year period. Additionally, drugs played a bigger role in pancreatitis at a high rate of 9.3% over the years. Additionally, it was seen that the administration of octreotide treatment decreased over the years.